Climate change: Perceived risk in agriculture and innovative adaptations at local level in Bundelkhand region of Madhya Pradesh - Pandey, A.K.; Prasad, Rajendra; Newaj, Ram; Dhyani, S.K.; Saroj, N.K.; Tripathi, V.D. (Indian Journal of Agroforestry, 2020)
Survey of 10 selected villages in Panna district of Bundelkhand region was conducted to assess perceived impact of climate change and farmers' adaptive initiations. The findings revealed that the farmers at local level had realized wide scale impact of climate change on agriculture and related activities. Deviation in weather pattern, occurrence of monsoon rain, wind and dust storm, and increase in unusual weather extremes put agricultural production system at risk. Change in phenology of crops manifested by deviation in flowering time & intensity, fruit-bearing pattern, and shape, size and quality of grain clearly indicated risk to biodiversity. Drawing from their traditional wisdom, farmers at local level had taken adaptation initiatives for minimizing risk in farming activities. Modification in sowing time of crops and cropping sequence according to monsoon rain, and adoption of agroforestry land use by planting trees on field boundaries and home-yard were the main adaptation strategies.